PRESENTLY FREQUENT OCCURRENCE OF CERVICAL PATHOLOGIES AND THEIR CAUSES (Western European Journal of Medicine and Medical Science, 2026)
Cervical pathologies are a group of diseases that are widespread among women of reproductive age. In recent years, the incidence of inflammatory diseases, dysplasia and cervical cancer has been increasing. This article analyzes the types, etiological factors, pathogenesis, risk factors and causes of their spread of cervical pathologies. The main etiological factors are human papillomavirus (HPV), early sexual life, polysexual intercourse, decreased immunity and lack of screening. Early diagnosis and preventive measures are important in reducing the incidence.